Effect of the application of inducers on soursop fruit (Annona muricata L.): postharvest disease control, physiological behaviour and activation of defense systems - R. González-Estrada, Efigenia M-González, Anelsy Ramos-Guerrero, Ramsés; Porfirio Gutiérrez-Martínez, Patricia Miranda-Castro (Emirates Journal of Food and Agriculture, 2019)
The application of chitosan (Chi) alone or in combination with methyl jasmonate (MJ) and salicylic acid (SA) in soursop infected with C. gloeosporioides and R. stolonifer in vivo as well as quality parameters (pH, total soluble solids, firmness and titratable acidity), respiration rate, ethylene production and defense related enzyme activities were investigated. Diseases caused by phytopathogenic fungi at postharvest stage are a serious problem throughout the world. The pathogens evaluated in this study were isolated from orchards in Nayarit, Mexico. The coating application of 1.0% Chi - 0.1 mM MJ - 6 mM SA on fruit inoculated with C. gloeosporioides and 0.5% Chi- 0.1 mM MJ on fruit inoculated with R. stolonifer were more effective to reduce the disease incidence and the extension of the lesion on soursop rather than the application of Chi, MJ or SA alone. In order to maintain quality parameters Chi and inducers were applied on fruits. During the storage time quality parameters of fruit were maintained. The respiration rate and ethylene production decreased with the application of the treatments combination. Higher activities of PPO (polyphenol oxidase), and POD (peroxidase) were evidenced with the combination of treatments compare to control. The application of chitosan, methyl jasmonate and salicylic acid is a suitable method for postharvest disease control of soursop during storage time as well as to maintain the fruit quality.